2022
DOI: 10.1111/jsr.13747
|View full text |Cite
|
Sign up to set email alerts
|

‘This is the last episode’: the association between problematic binge‐watching and loneliness, emotion regulation, and sleep‐related factors in poor sleepers

Abstract: Evidence on the relation between binge-watching and sleep quality is still scarce and inconsistent and none has taken into account both the healthy and pathological dimensions of the phenomenon. This study aimed at filling this gap by investigating both aspects in healthy participants with high and low sleep quality. Further, we aimed at identifying sociodemographic, psychological and sleep-related determinants of problematic binge-watching in poor sleepers. We first conducted independent comparisons between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Indeed, previous studies have linked a higher prevalence of insomnia with the female gender and being single ( Morin et al, 2011 ; Jung and Lee, 2016 ; Duran and Kaynak, 2022 ; Tsou, 2022 ). Additionally, poor sleep quality is associated with gender and emotional regulation ( Alfonsi et al, 2022 ). Lifestyle can also impact sleep patterns and habits ( Shochat, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have linked a higher prevalence of insomnia with the female gender and being single ( Morin et al, 2011 ; Jung and Lee, 2016 ; Duran and Kaynak, 2022 ; Tsou, 2022 ). Additionally, poor sleep quality is associated with gender and emotional regulation ( Alfonsi et al, 2022 ). Lifestyle can also impact sleep patterns and habits ( Shochat, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher level of studyholism was reported in females, which could be attributed to the fact that females exhibit higher levels of perfectionism in university performance ( Haase et al, 2013 ). Another contributing factor is that emotional dysregulation has been reported to be relevant to other types of addiction behavior, such as binge-watching behavior ( Alfonsi et al, 2022 ) and problematic internet use ( Usubini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NT1 patients may have coping mechanisms that alter emotional experiences to avoid cataplexy. Furthermore, sleep and emotion regulation have a bidirectional relationship [ 70 ], and poor sleep quality is associated with difficulties in emotion regulation and affective dysfunction [ 71 , 72 , 73 ]. Notably, disturbed nighttime sleep is a crucial feature of narcolepsy [ 74 ] that might negatively affect emotion regulation processes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, people may experience themselves as tired and exhausted, which affects their everyday life. According to Alfonsi et al (2023), problematic binge watching and daytime sleepiness are connected to a variety of factors that may impact and exacerbate both, creating a vicious cycle. Specifically, they observed that poor sleepers were more likely to binge watch to cope with negative sensations.…”
Section: Introductionmentioning
confidence: 99%